Addressing the Cybersecurity Issues and Needs of Rural Pennsylvania Nonprofit Organizations (Journal of The Colloquium for Information Systems Security Education, 2023)
The need for cybersecurity competence has become a strategic area for all types of organizations, be it large or small, for profit or nonprofit. This is an area of particular concern for smaller nonprofit organizations; and especially for those in rural areas with limited resources to address their cybersecurity risks. Cyber-attacks wreak havoc on the networks and systems for services provided to nonprofit consumers. The problems associated with various types of attacks, from outside nefarious individuals/groups or internal personnel, are particularly difficult for nonprofits in rural communities with limited resources for cybersecurity infrastructure and limited staff proficient in cybersecurity knowledge and skills. We have developed a cybersecurity assessment process to ascertain key needs and weaknesses with respect to cybersecurity for nonprofits in such rural communities in Pennsylvania. Additionally, this grant-sponsored work-in-progress research aims to provide guidance to rural nonprofits with “best practices” and related content that can be easily implemented despite their limitations.
Keywords: nonprofit; survey; Cybersecurity; rural